Turkish Translation and Cultural Adaptation of the Scale of Parental Perception of Children’s Exposure to Tobacco Smoke: A Validity and Reliability Study - Yaylaoglu, Seydanur; Dundar, Cihad (Addicta: The Turkish Journal on Addictions, 2024)
Abstract: Smoking not only poses a significant health risk to smokers but also endangers non-smokers, particularly children, through passive smoke exposure. We aimed to develop a Turkish version of the “Parental Perception of Children’s Exposure to Tobacco Smoke Scale” and evaluate its psychometric properties. The research involved 500 parents with children under 18 years of age who presented to family health centers between November 2022 and April 2023. The scale’s reliability was assessed through item–total score correlations, test–retest analysis, and Cronbach’s alpha coefficient, which yielded a high value of 0.937. Exploratory and confirmatory factor analyses, following Kaiser–Meyer–Olkin and Bartlett tests, revealed a four-factor structure. Scale scores were higher among women, healthcare professionals, individuals with higher education levels, and non-smokers. This newly validated and reliable scale serves as a valuable tool for evaluating parents’ perceptions of smoke exposure in children, aiding in the identification of effective interventions and the assessment of their impact.